2017
DOI: 10.1016/j.cma.2017.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Variational inequality approach to enforcing the non-negative constraint for advection–diffusion equations

Abstract: These figures depict the concentration profiles of the advection-diffusion equation under the Discontinuous Galerkin formulation (left) and the Discontinuous Galerkin formulation with bounded constraints enforced through a variational inequality (right). Only the regions where concentrations meet the threshold of 0.5 and above are shown. Abstract. Predictive simulations are crucial for the success of many subsurface applications, and it is highly desirable to obtain accurate non-negative solutions for transpor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 87 publications
0
21
0
Order By: Relevance
“…Here P p (E) denotes the space of polynomials in d variables of degree less than or equal to p over the element E, and Q p (E) is the space of d-dimensional tensor products of polynomials of degree less than or equal to p. The general form of the weak formulation for equation (15) can be written as follows: Find u h ∈ U h such that…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here P p (E) denotes the space of polynomials in d variables of degree less than or equal to p over the element E, and Q p (E) is the space of d-dimensional tensor products of polynomials of degree less than or equal to p. The general form of the weak formulation for equation (15) can be written as follows: Find u h ∈ U h such that…”
Section: Methodsmentioning
confidence: 99%
“…One of the most popular approaches undertaken is the development of sophisticated finite element packages like FEniCS/Dolfin [4,30], deal.II [3,9], Firedrake [35], LibMesh [25], and MOOSE [21] which provide application scientists the necessary scientific tools to quickly address their specific needs. Alternatively, stand alone finite element computational frameworks built on top of parallel linear algebra libraries like PETSc [7,8] may need to be developed to address specific technical problems such as enforcing maximum principles in subsurface flow and transport modeling [14,15,31] or modeling atmospheric and other geophysical phenomena [13,32], all of which could require field-scale or even global-scale resolutions. As scientific problems grow increasingly complex, the software and algorithms used must be fast, scalable, and efficient across a wide range of hardware architectures and scientific applications, and new algorithms and numerical discretizations may need to be introduced.…”
Section: Introductionmentioning
confidence: 99%
“…To find this scaling, start with the electrolyte domain because it is the most complex. Plugging the definition j e from (4) into the potential balance equation, (8), yields:…”
Section: Nondimensionalizationmentioning
confidence: 99%
“…Using the definitions of N s and j s from (1) and (2) in the concentration and potential balance equations, (6) and (8), with the new length and timescales results in the system:…”
Section: Nondimensionalizationmentioning
confidence: 99%
“…However, many scientific problems are often heterogeneous in nature, which may complicate the physics of the governing equations and may become more expensive to solve numerically. In the earlier work, it was shown that solving heterogeneous problems like chaotic flow resulted in suboptimal algorithmic convergence (ie, the iteration counts grew with h ‐refinement), so our goal is to demonstrate how physical properties such a heterogeneity and anisotropy may skew how we interpret the performance. Let us now assume that we have a heterogeneous and anisotropic diffusivity tensor that can be expressed as follows: boldDfalse(boldxfalse)=()centerarrayarrayαy2+z2+1arrayαxyarrayαxzarrayαxyarrayαx2+z2+1arrayαyzarrayαxzarrayαyzarrayαx2+y2+1, where α≥0 is a user defined constant that controls the level of heterogeneity and anisotropy present in the computational domain.…”
Section: Demonstration Of the Performance Spectrummentioning
confidence: 99%